Distributed Purchasing Asset Management - Jusoh, Norsiah (2003)
Distributed Purchasing Asset Management was developed as innovative effort to encourage flexibility between the purchasing departments and management. The system provides collaborative way and provided a better way in accessing information of asset, item, purchase order and invoice. This report has discussed the problem faces with current system. The system developed for purchaser department, it has several major components, which is asset, item, purchase order, invoice and searching. The user can add, edit, and delete the data uploaded from within the web page. this project, Distributed Purchasing Asset Department was developed with MySQl as the database back end and Hypertext Processor (PHP) as the web page scripting language. Since the information is keep on the distributed, it is stored and accessible anywhere or any time from other branch or whenever there us an internet connection. User can easily enter, update or searching by logging on to a web site. Security is maintained by the user of username and password. The user has their own if number which give them access the information